2022
DOI: 10.1038/s41557-022-00935-y
|View full text |Cite
|
Sign up to set email alerts
|

E- and Z-trisubstituted macrocyclic alkenes for natural product synthesis and skeletal editing

Abstract: Many therapeutic agents are macrocyclic trisubstituted alkenes, and yet, preparation of these structures is typically inefficient and nonselective. A possible solution would entail catalytic macrocyclic ring-closing metathesis, but these transformations require high catalyst loading, conformationally rigid precursors, and are often low yielding and/or non-stereoselective. Here, we introduce a ring-closing metathesis strategy for synthesis of trisubstituted macrocyclic olefins in either stereoisomeric form, reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…While classic reactions for alkene synthesis, such as the Wittig and Julia-Kocienski methods, are reliably used to prepare disubstituted alkenes, challenges associated with forming highly substituted (i.e., tri- and tetrasubstituted) alkenes using these methods limit their broad applicability. Efforts to enable the synthesis of highly substituted alkenes have resulted in the development of catalytic strategies based on olefin metathesis and cross-coupling . As an alternative approach, transition-metal catalysis has been applied to the synthesis of alkenes via the hydroalkylation of alkynes (Figure A).…”
mentioning
confidence: 99%
“…While classic reactions for alkene synthesis, such as the Wittig and Julia-Kocienski methods, are reliably used to prepare disubstituted alkenes, challenges associated with forming highly substituted (i.e., tri- and tetrasubstituted) alkenes using these methods limit their broad applicability. Efforts to enable the synthesis of highly substituted alkenes have resulted in the development of catalytic strategies based on olefin metathesis and cross-coupling . As an alternative approach, transition-metal catalysis has been applied to the synthesis of alkenes via the hydroalkylation of alkynes (Figure A).…”
mentioning
confidence: 99%
“…In contrast, there was 77% conversion to the trisubstituted enoate 3a (71% yield, 93:7 Z / E ) with Mo­(MAP)-2 (entry 2), which has a sterically less demanding aryloxide. When Mo­(MAP)-3 (entry 3), bearing a 2,3,5,6-tetraphenyl aryloxide, , was employed, formation of 3a was more efficient and more stereoretentive (81% yield and 97:3 Z / E ). A more striking trend involved the monoaryloxide chloride (MAC) complexes [entries 4–6, Table ; B­(C 6 F 5 ) 3 is to help dissociate the stabilizing pyridine ligand].…”
Section: Resultsmentioning
confidence: 99%
“…However, when Mo-1a was used, CM afforded only ∼15% E , E -10 (20% disappearance of E -12 ). A brief screening study indicated that with a bromine substituent at C4 of the aryloxide ligand, specifically, with Mo-3 , CM, which occurs only at the more electron rich trisubstituted olefin, is considerably more efficient. We were therefore able to isolate E , E -10 in 77% yield and 95:5 E : Z ratio and Z , E -10 in 68% yield and 97:3 E : Z .…”
Section: Resultsmentioning
confidence: 99%